Neutrophils exposed to bacterial lipopolysaccharide upregulate NADPH oxidase assembly. - F R DeLeo; J Renee; S McCormick; M Nakamura; M Apicella; J P Weiss; W M Nauseef (The Journal of Clinical Investigation, 1998)
Bacterial LPS is a pluripotent agonist for PMNs. Although it does not activate the NADPH-dependent oxidase directly, LPS renders PMNs more responsive to other stimuli, a phenomenon known as "priming." Since the mechanism of LPS-dependent priming is incompletely understood, we investigated its effects on assembly and activation of the NADPH oxidase. LPS pretreatment increased superoxide (O2-) generation nearly 10-fold in response to N-formyl methionyl leucyl phenylalanine (fMLP). In a broken-cell O2–generating system, activity was increased in plasma membrane-rich fractions and concomitantly decreased in specific granule-rich fractions from LPS-treated cells. Oxidation-reduction spectroscopy and flow cytometry indicated LPS increased plasma membrane association of flavocytochrome b558. Immunoblots of plasma membrane vesicles from LPS-treated PMNs demonstrated translocation of p47-phox but not of p67-phox or Rac2. However, PMNs treated sequentially with LPS and fMLP showed a three- to sixfold increase (compared with either agent alone) in plasma membrane-associated p47-phox, p67-phox, and Rac2, and translocation paralleled augmented O2- generation by intact PMNs. LPS treatment caused limited phosphorylation of p47-phox, and plasma membrane-enriched fractions from LPS- and/or fMLP-treated cells contained fewer acidic species of p47-phox than did those from cells treated with PMA. Taken together, these studies suggest that redistribution of NADPH oxidase components may underlie LPS priming of the respiratory burst.